The model of objects classifier of critical information infrastructure of the state - Корченко, Олександр Григорович; Дрейс, Юрій Олександрович; Романенко, Ольга Олександрівна; Бичков, Володимир Вячеславович (Ukrainian Information Security Research Journal, 2018)
Providing the process automation services in all spheres of human, society and state life support has led to increased demands for the information protection in information and telecommunication systems (ITS) of potentially dangerous objects of critical infrastructure of the state. In accordance with the existing legal and regulatory framework related to the objects of critical infrastructure, there is an incomplete-ness regarding the possibility of their proper classification, there is also no list of ITS of such objects and there are no criteria for the negative consequences assessment. Solving these issues will generate the formation of such objects clas-sifier of critical information infrastructure, which will enable the creation of conditions to increase their resilience to cyber attacks. Accordingly, a tool is proposed for classifying ob-jects of critical information infrastructure. The basis of its construction is a tuple model, the components of which are ordered identifiers of critical infrastructure objects that re-flect: the sector of the critical information infrastructure of the state; administrative territorial unit of Ukraine; name or identification number of the legal entity; form of ownership of the organization-owner / manager of ITS; the type of in-formation processed in the ITS; registration numbers of documents certifying the availability of certified/licensed systems or information security means; the negative conse-quences of cyber attacks on ITS. With the help of the pro-posed model, examples of objects classification of critical in-formation infrastructure of the state are presented, and it will give an opportunity to form a list of relevant ITS to ensure their priority protection against cyber attacks in future.